2009
DOI: 10.1080/00140130903197461
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between observed and perceived deviations from normative work procedures

Abstract: Deviations from anticipated courses of events are often associated with accidents, while the effects of deviations that decrease productivity but do not obviously lead to human injury are less clear. A systemic approach to production and safety is introduced, and it is proposed that production deviations have effects that may lead to safety violations and personal injury. In addition, the relationship between observed and perceived production deviations from 12 senior (60-79 years old) males' routine work usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Sometimes, the implementation of guidelines is hindered by organisational constraints 36. Sometimes people are simply unaware of their deviations 37. Thus, in the same way that errors cannot necessarily be avoided through ‘trying harder’, seeing violations of safety processes as purely due to individual will does not account for the systemic pressures upon the individuals delivering care.…”
Section: Compliance and Violations In Complex Systemsmentioning
confidence: 99%
“…Sometimes, the implementation of guidelines is hindered by organisational constraints 36. Sometimes people are simply unaware of their deviations 37. Thus, in the same way that errors cannot necessarily be avoided through ‘trying harder’, seeing violations of safety processes as purely due to individual will does not account for the systemic pressures upon the individuals delivering care.…”
Section: Compliance and Violations In Complex Systemsmentioning
confidence: 99%
“…Naturalistic observations in real work situations are required to get this insight (Lawton 1998, Phipps et al 2008. In a recent study, Lindroos (2009) compared observed and perceived deviations for different machine complexity and showed a positive relationship only for simple machines. For more complex machine work, it was difficult to match observers' and operators' perception of deviations.…”
Section: Introductionmentioning
confidence: 96%